Cinematic Rendering in Anatomy: A Crossover Study Comparing a Novel 3D Reconstruction Technique to Conventional Computed Tomography - Binder, Johannes; Scholz, Michael; Ellmann, Stephan; Uder, Michael; Grützmann, Robert; Krautz, Christian; Weber, Georg (Anatomical Sciences Education, 2020)
Integration of medical imaging into preclinical anatomy courses is already underway in many medical schools. However, interpretation of two-dimensional grayscale images is difficult and conventional volume rendering techniques provide only images of limited quality. In this regard, a more photorealistic visualization provided by Cinematic Rendering (CR) may be more suitable for anatomical education. A randomized, two-period crossover study was conducted from July to December 2018, at the University Hospital of Erlangen, Germany to compare CR and conventional computed tomography (CT) imaging for speed and comprehension of anatomy. Sixteen students were randomized into two assessment sequences. During each assessment period, participants had to answer 15 anatomy-related questions that were divided into three categories: parenchymal, musculoskeletal, and vascular anatomy. After a washout period of 14 days, assessments were crossed over to the respective second reconstruction technique. The mean interperiod differences for the time to answer differed significantly between the CR-CT sequence (-204.21 +/- 156.0 seconds) and the CT-CR sequence (243.33 +/- 113.83 seconds;P < 0.001). Overall time reduction by CR was 65.56%. Cinematic Rendering visualization of musculoskeletal and vascular anatomy was higher rated compared to CT visualization (P P = 0.003), whereas CT visualization of parenchymal anatomy received a higher scoring than CR visualization (P < 0.001). No carryover effects were observed. A questionnaire revealed that students consider CR to be beneficial for medical education. These results suggest that CR has a potential to enhance knowledge acquisition and transfer from medical imaging data in medical education.
CRIS-Team WoS Importer:2020-07-17

Collateral effects of the SARS-CoV-2 pandemic on oncologic surgery in Bavaria - Dienemann, Thomas; Brennfleck, Frank; Dejaco, Alexander; Grützmann, Robert; Binder, Johannes; Krautz, Christian; Stoess, Christian; Jaeger, Carsten; Friess, Helmut; Schlitt, Hans Juergen; Brunner, Stefan M. (BMC Surgery, 2021)
Background: The ongoing SARS-COV-2 pandemic has severe implications for people and healthcare systems everywhere. In Germany, worry about the consequences of the pandemic led to the deferral of non-emergency surgeries. Tumor surgery accounts for a large volume in the field of visceral surgery and cannot be considered purely elective. It is not known how the SARS-COV-2 pandemic has changed the surgical volume in tumor patients. Methods: Retrospective analysis of the amount of oncological surgeries in three academic visceral surgery departments in Bavaria, Germany, in 2020. Procedures were split into subgroups: Upper Gastrointestinal (Upper GI), Colorectal, Hepato-Pancreato-Biliary (HPB), Peritoneal and Endocrine. Procedures in 2020 were compared to a reference period from January 1st, 2017 to December 31st 2019. Surgical volume was graphically merged with SARS-COV-2 incidence and the number of occupied ICU beds. Results: Surgical volume decreased by 7.6% from an average of 924 oncologic surgeries from 2017 to 2019 to 854 in 2020. The decline was temporally associated with the incidence of infections and ICU capacity. Surgical volume did not uniformly increase to pre-pandemic levels in the months following the first pandemic wave with lower SARS-COV-2 incidence and varied according to local incidence levels. The decline was most pronounced in colorectal surgery where procedures declined on average by 26% following the beginning of the pandemic situation. Conclusion: The comparison with pre-pandemic years showed a decline in oncologic surgeries in 2020, which could have an impact on lost life years in non-COVID-19 patients. This decline was very different in subgroups which could not be solely explained by the pandemic.
CRIS-Team Scopus Importer:2021-12-17
Keywords: COVID-19; Oncologic surgery; Oncology; Patient care; SARS-CoV-2

Investigating the Effects of Selective Information Presentation in Intensive Care Units Using Virtual Reality - Theelke, Luisa; Metzler, Fynn-Lennardt; Kreimeier, Julian; Hauer, Christopher; Binder, Johannes; Roth, Daniel (2023 IEEE International Symposium on Mixed and Augmented Reality (ISMAR), 2023)
Medical personnel working in intensive care units (ICUs) are continuously exposed to a multitude of alarms emanating from various monitoring devices, such as cardiac monitors, ventilators, or infusion pumps. The sheer volume of alarms, coupled with high false positive rates, can lead to alarm fatigue. This phenomenon compromises patient safety and places an additional burden on nurses who must diligently prioritize and respond to alarms in the highly dynamic environment. While the testing of stress-reducing strategies in a real ICU is challenging, virtual reality (VR) represents a powerful tool and methodology to simulate an ICU environment and test optimization scenarios for alarm display strategies. For example, redistributing alarms to responsible individuals (personalized information presentation) has been proposed as a solution, but testing in real ICU environments is not applicable due to critical patient safety. In this paper, we present a VR simulation of an ICU to simulate comparable stress situations, as well as to assess the impact of a selective and personalized alarm representation strategy in an evaluation study in two conditions. A stress condition mirrors the current ubiquitous audible alarm distribution in most ICUs, where alarms are heard non-patient-specific throughout the ward. In an experimental condition, alarms are filtered patient-specific to reduce information overload and noise pollution. Our user study with medical personnel and novices shows that stress levels can be simulated with our system as indicated by physiological responses. Further, we show that the perceived task load can be reduced with selective information presentation. We discuss the potential benefits of ICU simulations as a methodology and personalized alarm distribution as a first potential strategy for future technologies in ICUs.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Human-centered computing-Human computer interaction (HCI)- Interaction paradigms-Virtual reality; Human-centered computing-Human computer interaction (HCI)-HCI design and evaluation methods-User studies

Ökonomische Auswirkung der COVID-19-Pandemie in der Allgemein- und Viszeralchirurgie: Ein Vergleich von Leistungs- und Erlösdaten zweier Kliniken aus Krankenhäusern unterschiedlicher Versorgungsstufen - Binder, Johannes; Brunner, Maximilian; Maak, Matthias; Denz, Axel; Grützmann, Robert; Krautz, Christian; Weber, Georg (Chirurg, 2021)
Background: During the first wave of the coronavirus disease 2019 (COVID-19) pandemic, German hospitals were required to limit the capacity for elective surgery to prevent the healthcare system from general overload. In March 2020, the German government passed the COVID-19 Hospital Relief Act that guaranteed compensation payments for these limitations. In this study the regional impact of this intervention were analyzed. Material and methods: The performance data and revenue figures for the departments of general and visceral surgery of the University Hospital of Erlangen (UKER) and the District Hospital St. Anna Höchstadt/Aisch (KKH) during the period from 1 April to 30 June 2019 were compared with the respective period in 2020. Results: There was a significant decrease in bed occupancy rates and case numbers of inpatient treatment. The latter declined by 20.06% in the UKER and 60.76% in the KKH. Nononcological elective surgery was reduced by 33.04% in the UKER and 60.87% in the KKH. The number of emergency procedures remained unchanged in the UKER, while they decreased by 51.58% in the KKH. The revenues from diagnosis-related groups (DRG) decreased by 22.12% (UKER) and 54% (KKH), respectively. After taking compensation payments and savings from variable material costs into account, the UKER recorded a loss of −3.87%, while there was a positive revenue effect of 6.5% in the KKH. Discussion: The nonselective restriction of elective surgery had a significant impact on patient care and revenue figures at both locations. With respect to the increase of intensive care capacities, such untargeted measures do not appear to be efficient. In addition, the fixed rate of compensation payments led to an unbalanced distribution of the financial aid between the two departments.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Coronavirus; DRG billing data; Hospital Relief Act; Surgery; Treatment quality

The opportunistic pathogen Aspergillus fumigatus coats its infectious propagules with antimicrobial peptides - Duemig, Michaela; Binder, Johannes; Gaculenko, Anastasia; Daul, F.; Hasenberg, M.; Gunzer, M.; Krappmann, Sven (2018)
EVALuna2:213342

The third dimension in perforator mapping—Comparison of Cinematic Rendering and maximum intensity projection in abdominal-based autologous breast reconstruction - Hauck, Theresa; Arkudas, Andreas; Horch, Raymund E.; Ströbel, Armin; May, Matthias; Binder, Johannes; Krautz, Christian; Ludolph, Ingo (Journal of Plastic Reconstructive and Aesthetic Surgery, 2022)
Background: Cinematic Rendering (CR) is a recently introduced post-processing three-dimensional (3D) visualization imaging tool. The aim of this study was to assess its clinical value in the preoperative planning of deep inferior epigastric artery perforator (DIEP) or muscle-sparing transverse rectus abdominis myocutaneous (MS-TRAM) flaps, and to compare it with maximum intensity projection (MIP) images. The study presents the first application of CR for perforator mapping prior to autologous breast reconstruction. Methods: Two senior surgeons independently analyzed CR and MIP images based on computed tomography angiography (CTA) datasets of 20 patients in terms of vascular pedicle characteristics, the possibility to harvest a DIEP or MS-TRAM flap, and the side of the flap harvest. We calculated inter- and intra-observer agreement in order to examine the accordance of both image techniques. Results: We observed a good inter- and intra-observer agreement concerning the type of flap and the side of the flap harvest. However, the agreement on the pedicle characteristics varies depending on the considered variable. Both investigators identified a significantly higher number of perforators with MIP compared with CR (observer 1, p<0.0001 and observer 2, p<0.0385). Conclusion: The current study serves as an explorative study, showing first experiences with CR in abdominal-based autologous breast reconstruction. In addition to MIP images, CR might improve the surgeon's understanding of the individual's anatomy. Future studies are required to compare CR with other 3D visualization tools and its possible effects on operative parameters.
CRIS-Team Scopus Importer:2022-03-11
Keywords: 3D visualization; Computed tomography angiography; DIEP; MS-TRAM